Lasioglossum bees – the forgotten pollinators. Issue 1 (1st January 2023) - Nelson, Warrick; Evans, Lisa; Donovan, Barry; Howlett, Brad
Abstract: Many ground-nesting bees are known contributors to crop pollination, but only a few specialist pollinating species are managed within agricultural systems. On the whole, most species (including the very large genus Lasioglossum ) have been ignored for their crop pollination contribution, largely because of their perceived inability to be effective pollinators. Lasioglossum species are globally very widespread, including across many different environmental and ecological niches. Scattered reports provide credible evidence that these commonly small bees are effective pollinators across a wide range of crops, particularly as they often nest in close aggregations and may be present in crops in large numbers. Given the frequency and flexibility of this genus as flower visitors of many crops, further research to assess their effectiveness as pollinators deserves much greater focus. This is starting to change as assessments begin highlighting their effectiveness as pollinators of a range of crops. Preliminary attention is now being placed on developing potential management (or at least population-influencing) practices to enhance their use.